Removal of Pharmaceuticals Phenolic Contaminants by Carbon Nanotubes from Waste Water as a Model of Health: A Review (International Journal of Psychosocial Rehabilitation, 2020)
Antibiotics, an important type of pharmaceutical pollutant, have attracted many researchers to the study of their removal from aqueous solutions. Emerging contaminants are of global concern due to the development of antibiotic-resistant genes potentially causing superbugs. Current wastewater treatment technology cannot sufficiently remove antibiotics from sewage; hence, new and low-cost technology is needed. Adsorptive materials have been extensively used for the conditioning, remediation, and removal of inorganic and organic hazardous materials. Carbon nanotube (CNT), a well-known carbon-based nanomaterial, has been widely used as a highly effective adsorbent for antibiotics because of its large specific surface area, high porosity, and favorable pore size distribution. Has drawn much attention in many application fields, including chemistry, in the last few decades. In this article, the performance of CNT towards two major types of antibiotics, phenolic contaminants such as amoxicillin and phenylephrine hydrochloride, was reviewed.